Investigating english education quality: Teacher factors in Cape Coast senior high schools. - Adobaw-Bnasah, A.; Lumadi, M. W. (South African Journal of Higher Education, 2025)
This study focused on teacher-related factors influencing the quality of English language education in senior high schools in Ghana’s Cape Coast Metropolis. It employed a mixed-methods approach, combining quantitative surveys with qualitative interviews and lesson observations. The research, guided by Input Evaluation Theory, gathered data from headmasters/mistresses and final-year students through a questionnaire to ensure unbiased responses. Additionally, semi-structured interviews were conducted with English teachers, and their lessons were observed. The findings revealed shortcomings in the quality of English education, with many English teachers lacking specialized training and showing deficiencies in content and pedagogical knowledge. The study recommends implementing professional development programs to equip teachers with essential skills and knowledge for effective instruction. English teachers are encouraged to create supportive, interactive learning environments that promote positive attitudes and enhance language learning experiences. These measures aim to address the identified challenges and ultimately improve the quality of English language education in senior high schools.